The Effect of Financial Targets and Financial Stability on Financial Statement Fraud in the Mining Sector Registered in LQ-45 for the 2019–2023 Period - Nurjanah, Cici; Foster, Bob; Musadat, Irfan Achmad (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2025)
This study aims to determine the picture and influence of Financial Targets and Financial Stability on financial statement fraud. This study uses a quantitative method with a descriptive and verifiable approach, the secondary data in this study is accessed through www.idx.co.id. The population of this study is companies in the mining sector listed in LQ-45 for the 2019-2023 period with a population of 50 financial statements from 10 companies during the 2019-2023 period. In the sampling process, the technique used is purposive sampling by producing 20 financial reports from 4 companies during the 2019-2023 period. Based on the results of the hypothesis test, it was obtained that the results of the t-test partially concluded that the Financial Target had no effect on Financial Statement Fraud with an effect of 0.1%. Meanwhile, the Financial Stability variabel partially did not affect Financial Statement Fraud with an influence of 3.0%. And simultaneously, Financial Targets and Financial Stability have no effect on financial statement fraud, the amount of influence is -0.70% on the Mining Sector Registered in LQ-45 for the 2019-2023 Period.